PRODUCT POSITIONING AND BRANDING - Agus Hasan Pura A (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
The goal of a positioning strategy is to create a product-price position attractive to target customers and good source of cash flow for the business. Product Positioning is at the core of every strong brand. A distinct and well - understood association exists between such a brand and its primary customer benefit. How it will create differentiated value for targeted segments and what position it want to occupy in those segments. Product positioning strategies are based on product differentiation, service differentiation and brand differentiation. Total benefits derived from this positioning must be larger than total cost of obtaining these benefits. Customers are influence by the status of a brand name or by the assurance of a well-known company (Lexus & Mercedes have strong brand association with prestige or status). A strong brand enhances positive evaluation; maintain a high of product awareness & provides a consistent image or brand personality;